2007
DOI: 10.1111/j.1442-2050.2007.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of body mass indices for patients undergoing esophagectomy for cancer

Abstract: The aim of this study was to determine the role of body mass index (BMI) in a Western population on outcomes after esophagectomy for cancer. Two hundred and fifteen consecutive patients undergoing esophagectomy for esophageal cancer of any cell type were studied prospectively. Patients with BMIs > 25 kg/m were classified as overweight and compared with control patients with BMIs below these reference values. Ninety-seven patients (45%) had low or normal BMIs, 86 patients (40%) were overweight, and a further 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
3
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 15 publications
6
30
3
1
Order By: Relevance
“…33,46,48 Overweight and obese patients showed conflicting results regarding long-term survival. Studies in vascular surgery, 45 oncology surgery 29,30 and cardiac surgery 37 reported survival benefit for overweight and obese patients, whereas other studies in oncology surgery 25 and cardiac surgery 47 did not demonstrate any association with long-term survival. Table 2 gives an overview of different patient populations in which an inverse relationship between BMI and mortality was demonstrated.…”
Section: The Risks Of Obesity In the Surgical Patientmentioning
confidence: 83%
“…33,46,48 Overweight and obese patients showed conflicting results regarding long-term survival. Studies in vascular surgery, 45 oncology surgery 29,30 and cardiac surgery 37 reported survival benefit for overweight and obese patients, whereas other studies in oncology surgery 25 and cardiac surgery 47 did not demonstrate any association with long-term survival. Table 2 gives an overview of different patient populations in which an inverse relationship between BMI and mortality was demonstrated.…”
Section: The Risks Of Obesity In the Surgical Patientmentioning
confidence: 83%
“…17 A more recent study from Europe found that BMI >25 kg/m 2 was not associated with worse outcomes in 215 patients undergoing oesophagectomy for cancer; specifically, there were no differences in operative times (median 280 min in both normal or high BMI), morbidity (49% vs 53%, p=0.4), mortality (8.3% vs 3.4%, p=0.1) and median number of harvested lymph node (14 vs 11, p=0.054). 18 Two recent studies by Blom et al 19 and Grotenhius et al 20 have both demonstrated that patients with elevated BMI do not experience an increase in operative outcomes or oncological outcomes. However, Blom and colleagues did demonstrate an increase in anastomotic leaks in the obese population, a finding which we did not corroborate.…”
Section: Discussionmentioning
confidence: 98%
“…A few reports that specifically focused on BMI suggested that pretreatment BMI was not associated with differential outcome with regard to OS or DFS. [12][13][14] However, the largest study to date is by Trivers et al 17 18 demonstrated that a BMI of >18 kg/m 2 was one of the independent prognostic factors in 105 patients treated with definitive chemoradiotherapy (P ¼ .003). However, in this study, the cutpoint for BMI was nontraditional and the sample size was small.…”
Section: Discussionmentioning
confidence: 99%
“…8 High BMI is a risk factor for gastroesophageal reflux disease (GERD) and, consequently, for EAC. [9][10][11] Several studies have reported that high BMI was not associated with improved or reduced overall survival (OS) after esophagectomy, [12][13][14] although increased postoperative morbidity, such as respiratory complications, anastomotic leaks, and length of hospital stay, have been associated with high BMI in patients with gastroesophageal cancer who are undergoing surgery. 14,15 Many of these studies included small number of patients, in whom adjunctive therapy (preoperative chemotherapy and/or radiotherapy) was used.…”
mentioning
confidence: 99%